O uso da semiótica em artigos brasileiros que estudam a marca: uma revisão de literatura (2008-2017) (Publicatio UEPG: Ciências Sociais Aplicadas, 2024)
Semiotic studies have sought to understand the construction of meaning by brands since the 1960s. Over the years, communication scientists have intensified these studies with adoption of French discursive semiotics as well as methodologies of American semiotics. The article tries to understand the Brazilian production, in the last ten years (2008-2017), in articles published in scientific journals. After searching on national and international indexers, 21 articles were cataloged and, based on them, it was sought to gather information about who scientists produced them, which institution are linked, which corpus studied, which semiotic methodology applied, and which authors were most cited. What is expected as relevant as a mapping for the purpose of developing this field of communication studies.